Interfaces in service modularity: A typology developed in modular health care provision. Issue 4 (18th March 2014) - de Blok, Carolien; Meijboom, Bert; Luijkx, Katrien; Schols, Jos; Schroeder, Roger
Abstract: We conduct case research in a particular service context, i.e. the sector for elderly care, in order to explore characteristics of interfaces and the role they play in service customization. Even though the study of modularity in areas other than goods production is increasing, little is known about interfaces outside the context of modular goods. From our case research, it follows that interfaces can be distinguished at the component level (linkages between components' contents) and at the service package level (linkages between service providers involved). The contribution of the paper is a first typology on interfaces in modular services. Four interface categories are distinguished, which offer a specification of the interfaces' function in creating variety and coherence, when linking content components as well as service providers. In addition, we provide a new definition of interfaces for services that differs from the accepted manufacturing definition.